Emotional Quotient dalam Pendidikan Islam - Sudirman Sudirman (SCHOLASTICA: Jurnal Pendidikan dan Kebudayaan, 2019)
One important component to be able to live in the midst of the community is the ability to direct the emotions well. Research conducted by Goleman shows that the contribution to the success of one’s IQ is only about 20% of the remaining 80% is determined by the cognate factor called emotional intelligence. In fact now it can be seen that the high IQ is not necessarily successful and not necessarily a happy life. People who are high IQ but because emotionally unstable and irritability are often mistaken in determining and solving the problems of life because they cannot concentrate. Emotions are not growing, not overwhelmed, often make change in the face of problems and be- have towards others so much conflict. Emotions are less processed also easily lead to others that sometimes are very excited agree on anything, but in a short time changed reject, so that disrupt the agreed cooperation with others. Thus, the man failed. Islamic education has a high attention to this. It can be seen from the Islamic educational task is to guide and direct the growth and human development from stage to stage of life of the students to achieve the optimal performance point. Attention Islamic education on IQ and EI because Islamic education has a major influence in the growth of education, knowledge, and reason.